Decreased sexual desire in aging male in Lapangan Puputan Niti Mandala Renon 2018 - Mohd Fauzan Arif Bin Mat Nudin; I Nyoman Gede Wardana; I Gusti Ayu Widianti (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2018)
Background: Aging changes are shown from the sub-atomic to the organismic level; ecological variables influence trial perceptions; optional impacts convolute clarification of essential systems; and correctly characterized, effectively quantifiable biomarkers are inadequate. Nobody bringing together hypothesis may exist, since the components of aging could be very distinct in various living beings, tissues, and cells. Method: This is a descriptive-observational study, which is aimed to evaluate the influence of aging on sexual desire in a male. The target population of this study is the men aged 50 years old and older in Lapangan Puputan Niti Mandala Renon, Denpasar Selatan, Bali from April 2018 to mei 2018 were involved in this research. Instruments that were used in this research is The Decreased Sexual Desire Screener questionnaire to assess the sexual function in older men. Result: This study showed that among 135 respondents aged 50 years old and older, through a questionnaire, most of the respondents stated that they have changing sexual desire. But, most of them are from the age group of 55-60 years old and 61-65 years old. People in the group of 50-55 years old less likely to experience a decrease in sexual desire compared to the older group. Conclusion: Older age influence sexual function in men.